Peranan Pendidikan dalam Memepersiapkan Sumber Daya Manusia di Era Informasi dan Pengetahuan - Imas Cintamulya (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2012)
Education has an important role in the information age and knowledge, which in this era of rapid change in many areas of life. Mind, knowledge, and the organization is a prominent factor in the era of information and knowledge. Educational institution should be able to prepare the profile of graduates who have the competencies relevant to the new age or information age. Some of the competencies necessary to be able to survive in the information age and knowledge are: 1) critical thinking ability and willingness to work hard, (2) creativity, (3) kalaborasi, (4) cross-cultural understanding, (5) communication, (6) operates a computer, (7) ability to learn independently. In this regard it is in science education should be reinforced with mathematics as a way of thinking of science, science laboratories equipped, the education of creativity, development of digital education.